Efficacy and safety of chemoradiation therapy compared with chemotherapy for esophageal carcinoma: An updated meta-analysis of randomized controlled trials. Issue 47 (November 2017) - Liu, Jinyuan; Xue, Lei; Zhen, Fuxi; Luo, Jinhua
Abstract: Background: The role of the chemoradiation therapy (CRT) and chemotherapy (CT) in the treatment of esophageal carcinoma (EC) remains controversial. Therefore, we conducted this meta-analysis to compare the efficacy and safety of CRT with CT in the treatment of EC patients. Methods: PubMed, Embase, Web of Science, and The Cochrane library were systematically reviewed for randomized controlled trials (RCTs) that compared CRT with CT. Outcomes included overall survival (OS), progression-free survival (PFS), pathological complete response (pCR), R0 resection, recurrence rate, mortality rate, and adverse events. Pooled estimates were expressed with hazard ratio (HR) with 95% confidence intervals (95% CIs) and risk ratio (RR) with 95% CIs. Results: Eight RCTs involving 1274 patients were included in this meta-analysis. Compared with CT, CRT was not associated with significantly improved OS (HR = 0.91, 95% CI: 0.82, 1.01; P = .072) and PFS (RR = 3.62, 95% CI: 1.10, 11.95; P = .035). The pCR rate and R0 resection rate were significant higher in the CRT group than that in the CT group (RR = 3.62, 95% CI: 1.10, 11.95, P = .035; RR = 1.18, 95% CI: 1.09, 1.27, P < .001; respectively). EC patients who received CRT had a higher mortality rate (RR = 2.50, 95% CI: 1.14, 5.48; P = .022) than those treated with CT, and the incidence of grade 3 or 4 adverse events was similar between the 2 groups (RR = 0.91, 95% CI: 0.62, 1.32; P = .612). Conclusion: On the basis of the current evidence, our results suggested that CRT seemed to have benefit in the radical resection, but no effect in the survival benefits. Further large-scale, well-conducted RCTs are needed to verify our findings.